Non-clinical community interventions: a systematised review of social prescribing schemes. Issue 2 (4th May 2018) - Chatterjee, Helen J.; Camic, Paul M.; Lockyer, Bridget; Thomson, Linda J. M.
Abstract: Background: This review focused on evaluation of United Kingdom social prescribing schemes published in peer-reviewed journals and reports. Schemes, including arts, books, education and exercise "on prescription" refer patients to community sources of non-clinical intervention. Method: A systematised review protocol appraised primary research material evaluating social prescribing schemes published 2000–2015. Searches were performed in electronic databases using keywords, and articles were screened for evaluation of patient data, referral process, assessment method and outcomes; non-evaluated articles were excluded. Results: Of 86 schemes located including pilots, 40 evaluated primary research materials: 17 used quantitative methods including 6 randomised controlled trials; 16 qualitative methods, and 7 mixed methods; 9 exclusively involved arts on prescription. Conclusions: Outcomes included increase in self-esteem and confidence; improvement in mental well-being and positive mood; and reduction in anxiety, depression and negative mood. Despite positive findings, the review identifies a number of gaps in the evidence base and makes recommendations for future evaluation and implementation of referral pathways.